Effects of the Pleistocene on the mitochondrial population genetic structure and demographic history of the silky shark (Carcharhinus falciformis) in the western Atlantic Ocean - Domingues, Rodrigo R. [UNESP]; Hilsdorf, Alexandre W. S.; Shivji, Mahmood M.; Hazin, Fabio V. H.; Gadig, Otto B. F. [UNESP] (Springer Nature, 2018)
The silky shark, Carcharhinus falciformis, is a large-bodied, oceanic-coastal, epipelagic species found worldwide in tropical and subtropical waters. Despite its commercial importance, concerns about overexploitation, and likely ecological significance of this shark as an upper trophic-level predator, understanding of its population dynamics remains unclear for large parts of its distribution. We investigated the genetic diversity, population structure and demographic history of the silky shark along the western Atlantic Ocean based on the use of 707 bp of the mitochondrial DNA control region (mtCR). A total of 211 silky sharks were sampled, originating from five areas along the western Atlantic Ocean. The mitochondrial sequences revealed 40 haplotypes, with overall haplotype and nucleotide diversities of 0.88 (± 0.012) and 0.005 (± 0.003), respectively. The overall population structure was significantly different among the five western Atlantic Ocean regions. Phylogenetic analysis of mtCR sequences from globally sourced silky shark samples revealed two lineages, comprising a western Atlantic lineage and western Atlantic—Indo-Pacific lineage that diverged during the Pleistocene Epoch. In general, tests for the demographic history of silky sharks supported a population expansion for both the global sample set and the two lineages. Although our results showed that silky sharks have high genetic diversity, the current high level of overexploitation of this species requires long-term, scientifically informed management efforts. We recommend that fishery management and conservation plans be done separately for the two western Atlantic matrilineal populations revealed here.
Keywords: Elasmobranch; Fisheries management; Gene flow; Genetic diversity; Marine connectivity; Phylogeography